PENGGUNAAN AIR KELAPA DALAM MEDIA KULTUR JARINGAN PISANG - Astutik Astutik (Universitas Tribhuwana Tunggadewi, 2008)
The objectives of this research were to study and to find out the influence of various liquidity in tissue culture’s media of banana toward the development of banana’ meristem, and to obtain a precisely coconut pond concentration in media of tissue culture resulted in the best plantlet. Treatments employed for this study comprised two factors. Liquidity of coconut pond as the first factor consisted of four levels, i.e. 0 % (A0), 7,5 % (A1), 15 % (A2) and 22,5 % (A3). Varieties of banana as the second factors consisted of Kepok (P1) and Ambon (P2). Parameters observed were initiation of rhizomes, number of rhizomes, number of leaves, root initiation, and number of roots. The results indicated that there were interactions between the liquidities of coconut ponds and variety of bananas during rhizomes initiation, number of leaves, period of root initiation and number of roots. The liquidities of coconut ponds in the concentration of 7,5 % and 15 % resulted in better rhizomes quality than other solutions. Whereas the liquidity of 7,5 % resulted in best quality of rhizomes initiation and number of leaves in Ambon variety. Best root initiation and number of roots was observed at 15 % liquidity of coconut pond treatment